2007
DOI: 10.1021/bi6025209
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Chymotrypsin by a Complex of Ortho-Vanadate and Benzohydroxamic Acid:  Structure of the Inert Complex and Its Mechanistic Interpretation

Abstract: Serine proteases, like serine beta-lactamases, are rapidly and covalently inhibited by suitably designed phosph(on)ates. The active sites of these enzymes must, therefore, be able to stabilize the pentacoordinated transition states of phosphyl transfer reactions as well as the tetrahedral transition states of acyl transfers. It follows that these enzymes should also be inhibited by molecules capable of generating inert pentacoordinated species. We (J.H.B. and R.F.P.) have previously shown that these enzymes ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…The localization of the phenyl ring of the hydroxamate in the S1 binding pocket and the hydroxamate oxygen is discussed by the authors. Globally, the study concludes that chymotrypsin and vanadate(V) are good models for studies involving protease inhibitors due to their ability to unravel the structural details of the catalytic transition states [450].…”
Section: Chymotrypsinmentioning
confidence: 94%
See 2 more Smart Citations
“…The localization of the phenyl ring of the hydroxamate in the S1 binding pocket and the hydroxamate oxygen is discussed by the authors. Globally, the study concludes that chymotrypsin and vanadate(V) are good models for studies involving protease inhibitors due to their ability to unravel the structural details of the catalytic transition states [450].…”
Section: Chymotrypsinmentioning
confidence: 94%
“…25). The V-atom presents a distorted octahedral geometry with six ligands: the mentioned serine, the carbonyl and hydroxyl of the benzohydroxamic acid and three O-atoms, one of which is hydrogen bonded to the backbone N-atom of Gly193 and Ser195 residues [450]. The localization of the phenyl ring of the hydroxamate in the S1 binding pocket and the hydroxamate oxygen is discussed by the authors.…”
Section: Chymotrypsinmentioning
confidence: 99%
See 1 more Smart Citation
“…Crystals of -chymotrypsin failed to form using previously published conditions (Stoddard et al, 1990). Further screening using Additive Screen (Hampton Research, Aliso Viejo, California, USA) demonstrated that supplementation of the previously reported condition (Stoddard et al, 1990) with sodium iodide was sufficient to produce large crystals of -chymotrypsin (Moulin et al, 2007). Crystal size was further increased using a modified sitting-drop technique in which an uncapped 0.5 dram vial was nested in a tightly sealed scintillation vial.…”
Section: Crystallizationmentioning
confidence: 99%
“…The systems of NH 4 VO 3 /H 2 O 2 /histidine-like ligands as models to imitate the active site of haloperoxidases have been explored by Conte and co-workers [14,16]. Pratt and co-workers investigated the formation and structures of complexes between vanadates and hydroxamic acids at neutral pH, and their mechanism of inhibition of ␤-lactamase [17][18][19]. Although much effort has been expended on investigating the complicated structures and chemical behaviors of diperoxovanadates in solution, there are still problems not completely elucidated owing to the complexity of vanadium chemistry.…”
Section: Introductionmentioning
confidence: 99%